2007
DOI: 10.1518/001872007x249965
|View full text |Cite
|
Sign up to set email alerts
|

Multisensory In-Car Warning Signals for Collision Avoidance

Abstract: Objective: A driving simulator study was conducted in order to assess the relative utility of unimodal auditory, unimodal vibrotactile, and combined audiotactile (i.e., multisensory) in-car warning signals to alert and inform drivers of likely front-to-rear-end collision events in a situation modeled on real-world driving. Background: The implementation of nonvisual in-car warning signals may have important safety implications in lessening any visual overload during driving. Multisensory integration can provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
126
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 197 publications
(139 citation statements)
references
References 53 publications
12
126
0
1
Order By: Relevance
“…While both unimodal and bimodal alerts are capable of attracting attention in undistracted conditions, bimodal alerts show increased benefit during tasks that induce high perceptual load (Botta et al, 2011;Chan & Chan, 2006;Ho, Reed, & Spence, 2007;Ho, Santangelo, & Spence, 2009;Santangelo & Spence, 2007). For example, Santangelo and Spence (2007) found that when participants were engaged in a perceptually demanding central rapid serial visual presentation task, bimodal cues aided detection of peripheral visual targets more than unimodal signals.…”
Section: Introductionmentioning
confidence: 99%
“…While both unimodal and bimodal alerts are capable of attracting attention in undistracted conditions, bimodal alerts show increased benefit during tasks that induce high perceptual load (Botta et al, 2011;Chan & Chan, 2006;Ho, Reed, & Spence, 2007;Ho, Santangelo, & Spence, 2009;Santangelo & Spence, 2007). For example, Santangelo and Spence (2007) found that when participants were engaged in a perceptually demanding central rapid serial visual presentation task, bimodal cues aided detection of peripheral visual targets more than unimodal signals.…”
Section: Introductionmentioning
confidence: 99%
“…The lead vehicle's brake lights were deactivated. This was a similar scenario to those used in previous studies (e.g., Ho, Reed & Spence, 2007).…”
Section: Apparatus and Materialsmentioning
confidence: 76%
“…Therefore, it is interesting to ask whether there will be similar age effects for informative collision warning signals. The second aim of the present study was to investigate whether multisensory informative warnings produce any additional BRT benefits relative to unimodal warnings, as have been shown in the case of non-informative warnings (e.g., Ho, Reed & Spence, 2007).…”
Section: Aims Of the Present Studymentioning
confidence: 99%
“…Visual-auditory HMIs have traditionally been used in the design of warnings as the multimodal presentation of warning signals usually speeds up the cognitive processes involved in the selection and execution of an appropriate response, such as braking or steering [46,47]. The advantageous effect of presenting more than one stimulus at once that Journal of Advanced Transportation requires a reaction, the so-called redundancy gain, has been demonstrated repeatedly in cognitive psychology research [48,49].…”
Section: Studymentioning
confidence: 99%